Protective Effects of Phytochemicals against Cardiac Hypertrophy by Modulating Oxidative Stress and Inflammation: A Review - Nasiruddin, Nalban (Pharmacognosy Reviews)
When heart undergoes increased work load, as a compensatory mechanism size of myocyte increases, this is denoted as cardiac hypertrophy (CH). If this condition is sustained for long term, it may lead to heart failure. Drugs used to treat this condition are associated with adverse drug reactions and there is a need of new drugs to combat hypertrophy. Subsequently, this concern has encouraged interest in the use of natural products, which may be better tolerated. Many studies have investigated the cardioprotective effect of phytochemicals against CH by abrogating oxidative stress and inflammation. This review concisely introduces the role of oxidative stress and inflammation in the progression of CH, and then enlighten the progress of phytochemicals towards its treatment. We highlight the promising applications and mechanisms of action of phytochemicals towards the treatment of CH in both in vitro and in vivo studies.
Keywords: Cardiac hypertrophy; Cardiac diseases; Oxidative stress; Inflammation; Phytochemicals